Bovine Amnion–Alginate Sponge (BAAS) as A Modern Wound Dressing: Pilot Study of Functional Groups, Basic Fibroblast Growth Factor, and Interleukin-6 Level - Hutagalung, Muhammad Bayu Zohari; Prajasari, Tabita; Eljatin, Dwinka Syafira; Edward, Mouli; Suroto, Heri (Scripta Medica, 2025)
Background/Aim: Chronic wounds are a significant health burden, impacting millions globally and incurring high healthcare costs. Bovine amnion membrane (BAM) offers anti-inflammatory, antimicrobial properties and bioactive growth factors, making it a promising candidate for wound healing applications. At the same time, alginate enhances the stabilisation and delivery of growth factors. This study aimed to characterise a bovine–amnion–alginate sponge (BAAS) by analysing its functional groups and evaluating the interleukin-6 (IL-6) and basic fibroblast growth factor (bFGF) levels in different ratios. Methods: A laboratory-based experimental study with a randomized, post-test-only design was conducted. BAAS at ratios of 25 %: 75 %, 50 %: 50 % and 75 %: 25 % were crosslinked with CaCl₂. The Fourier transform infrared spectroscopy (FTIR) was used to assess functional groups and provide insights into the molecular composition of the samples. Meanwhile, the biomolecules of IL-6 and bFGF levels were quantified using enzyme-linked immunosorbent assay (ELISA). Results: Chemical functional group analysis using FTIR confirmed ionic bonding between Ca²⁺ ions and carboxylate groups, glycosidic stability and enhanced hydrophilicity in BAM-rich formulations. IL-6 levels were 45, 49 and 56 pg/mL, while bFGF levels were 42, 46 and 52 pg/mL for BAM-alginate ratios of 25 %: 75 %, 50 %: 50 % and 75 %: 25 %, respectively. No IL-6 or bFGF was detected in the pure alginate control. Conclusion: BAAS formulations demonstrate the interplay between functional groups identified in FTIR spectra and cytokine/growth factor modulation observed in ELISA as evidence that its composition can be tailored to address specific phases of wound healing.